2019
DOI: 10.1016/j.chest.2019.01.036
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of High-Speed Video Analysis to Diagnose Primary Ciliary Dyskinesia

Abstract: BACKGROUND: Diagnosis of primary ciliary dyskinesia (PCD) relies on a combination of tests. High-speed video microscopy analysis (HSVA) is widely used to contribute to the diagnosis. It can be analyzed on the day of diagnostic consultation, but the qualitative analyses are subjective. Diagnostic accuracy and reliability of assessing ciliary function have not been robustly evaluated. We aimed to establish the accuracy of HSVA to diagnose PCD compared with a combination of tests, and to assess the interobserver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
71
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 71 publications
(77 citation statements)
references
References 26 publications
1
71
0
5
Order By: Relevance
“…Nasal nitric oxide gas is reduced in most patients with PCD [10]. Analysis of the respiratory epithelium by nasal brushing can be used for identification of ciliary structural defects by transmission electron microscopy (TEM) [113,118] and defects of the ciliary beat pattern and frequency can be identified by high-speed video microscopy analysis (HSVMA) [107]. HSVMA has excellent sensitivity and specificity for PCD and particular beat patterns have been linked to specific ultrastructural defects [15].…”
Section: Current Pcd Diagnosticsmentioning
confidence: 99%
“…Nasal nitric oxide gas is reduced in most patients with PCD [10]. Analysis of the respiratory epithelium by nasal brushing can be used for identification of ciliary structural defects by transmission electron microscopy (TEM) [113,118] and defects of the ciliary beat pattern and frequency can be identified by high-speed video microscopy analysis (HSVMA) [107]. HSVMA has excellent sensitivity and specificity for PCD and particular beat patterns have been linked to specific ultrastructural defects [15].…”
Section: Current Pcd Diagnosticsmentioning
confidence: 99%
“…Currently, there is no single gold standard test which will diagnose every patient with PCD, and international guidelines recommend a panel of a variety of tests to diagnose PCD . According to the European Respiratory Society (ERS) guidelines, hallmark ciliary ultrastructural defects assessed by transmission electron microscopy (TEM) and bi‐allelic mutations in known PCD causing genes can confirm a diagnosis, but will miss the diagnosis in between 15%‐30% of patients with PCD. Ciliary functional analysis using digital high‐speed video microscopy (DHSV) is used internationally as part of the diagnosis of patients suspected of having PCD .…”
Section: Introductionmentioning
confidence: 99%
“…However, this may be an over‐estimation of diagnostic accuracy: DHSV was either compared with incomplete reference standards (mainly TEM alone), or to a reference standard including DHSV. A recent retrospective cohort study reported an excellent sensitivity (100%) and specificity (96%) for DHSV to diagnose PCD against the ERS guidelines, but cases with normal TEM or genotyping may not have been identified.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations